EXPEDIENTE - v15n3 - Soares, Adriana Benevides; Tsallis, Alexandra Cleopatre; Mendes, Deise Maria Leal Fernandes; Valentim, Renata Patrícia Forain de; Barros, Rita Maria Manso de (Estudos e Pesquisas em Psicologia, 2015)
EXPEDIENTE - v15n3